2006
DOI: 10.2337/diabetes.55.04.06.db05-0927
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and Stable Pancreatic Gene Transfer by Adeno-Associated Virus Vectors via Different Routes

Abstract: Diabetes is a disease of epidemic proportions and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(173 citation statements)
references
References 43 publications
9
164
0
Order By: Relevance
“…28 Expression can be further restricted within the islet by coupling transgene expression to activation of the MIP, 28 thereby providing an opportunity to specifically target the expression of therapeutic genes within beta-cells. AAV vectors represent an innovative gene therapy tool, having reduced immunogenicity compared with that of adenoviruses, 36 while being capable of directing long-term expression of transgenes both in humans and in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Expression can be further restricted within the islet by coupling transgene expression to activation of the MIP, 28 thereby providing an opportunity to specifically target the expression of therapeutic genes within beta-cells. AAV vectors represent an innovative gene therapy tool, having reduced immunogenicity compared with that of adenoviruses, 36 while being capable of directing long-term expression of transgenes both in humans and in mice.…”
Section: Discussionmentioning
confidence: 99%
“…33 The observation that the majority of GLP-1-positive beta-cells are located in the periphery of the islet, is consistent with the intraperitoneal delivery route and has been observed previously for DsAAV8-mediated transgene expression in islets. 28 To investigate the mechanisms contributing to improved glucose tolerance in mice receiving DsAAV8-MIP-GLP-1, a pancreatic morphometric analysis was performed. Animals expressing beta-cell GLP-1 had similar total insulin-positive area (0.0033 ± 0.0004 in GLP-1-treated animals versus 0.0026 ± 0.0007 in control animals), but trended toward an increase in the total number of insulin-positive areas per mm 2 of pancreatic tissue (15.9 ± 1.5 versus 11.4 ± 1.9 in control animals; P ¼ 0.097) due to significant increase in the number of small insulin-positive clusters (Figures 5a and b).…”
Section: In Vivo Expression Of Glp-1 Increases Beta-cell Proliferatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblast growth factor receptor, αvβ5 integrin, and hepatocyte growth factor receptor have been reported to work as co-factors [3638]. Among the many types of AAV, single-stranded AAV, such as serotypes 8 (AAV-8) and 9 (AAV-9), and double-stranded AAV have been reported to have effective transduction of transgenes into the pancreas [3944]. …”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%
“…In terms of administration routes of viral vectors for the delivery of transgenes to the pancreas in vivo , although intravenous administration has been used most often, intrapancreatic ductal injections might be more efficient because transgenes with viral vectors can more easily escape from phagocytes in the liver via this administration route [51]. The transduction efficiency of transgenes with viral vectors in the pancreas via intravenous administration was reported to improve under conditions of reduced blood flow to the liver, such as with a liver bypass or transient blockade of liver circulation [44,52]. However, other studies have reported that intravenous administration of AAV-8 or AAV-9 substantially delivered transgenes to the pancreas [40,53].…”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%